Teaching business studies in the visual era - Roberts, David (Henry Stewart Talks, 2017)
‘Pictorial turn’, ‘Death by PowerPoint’, Multimedia learning, Imagery and pedagogy, Business entrepreneurship in post-conflict spaces, Evaluating learning methods, Online sources of images